Performance enhancement of asymmetric filtered 40 Gb/s carrier suppressed return to zero‐differential phase shift keying receiver in a 50 GHz grid. Issue 1 (1st February 2013) - Olubodun, Olugbenga Ajijola; Murray, Neil Joseph; Harper, Paul; Doran, Nicholas John
Abstract : The authors present the impact of asymmetric filtering of strong (e.g. 35 GHz) optical filters on the performance of 42.7 Gb/s 67% (carrier suppressed return to zero)‐differential phase shift keying systems. The performance is examined (in an amplified spontaneous emission (ASE) noise‐limited regime and in the presence of chromatic dispersion) when offsetting the filter at the receiver by substantial amounts via balanced, constructive and destructive single‐ended detections. It is found that with a slight offset (vestigial side band) or an offset of almost half of the modulation frequency (single‐side band), there is a significant improvement in the calculated ' Q '.